Post‐IFRS Revaluation Adjustments and Executive Compensation - Chen, Kevin C. W.; Tang, Feng (Contemporary Accounting Research, 2017)
Abstract International Financial Reporting Standards ( IFRS ) allow firms to record adjustments (gains or losses) from the revaluation of investment properties in their income statements. After Hong Kong adopted IFRS in 2005, property companies were required to move their revaluation gains and losses ( RGL ) from equity to income. We find RGL to be a significant determinant of executive compensation in these firms after 2005, but not before. We further find evidence that the RGL ‐compensation association is driven by firms with relative weak corporate governance structure, such as firms in which the controlling shareholders own a relatively small percentage of shares, firms in which the controlling shareholders have control rights that exceed ownership rights, and firms that are no longer run by their founders.